Risk Management for Engineering Projects Procedures, Methods and Tools - Munier, Nolberto (Springer International Publishing : Imprint: Springer, 2014)
Many people see risk in engineering projects as an imprecise and nebulous problem - something that exists, is feared and is impossible to deal with. Nothing could be further from the truth. While risk is certainly ubiquitous, sometimes difficult to detect, and cannot always be completely avoided, it can generally be mitigated, reduced or prevented through timely analysis and action.   This book covers the entire process of risk management by providing methodologies for determining the sources of project risk, and once threats have been identified, managing them through:   ·         identification and assessment (probability, relative importance, variables, risk breakdown structure, etc.) ·         implementation of measures for their prevention, reduction or mitigation ·         evaluation of impacts and quantification of risks ·         establishment of control measures   It also considers sensitivity analysis to determine the influence of uncertain parameters values on different project results, such as completion time, total costs, Internal Rate of Return, etc.   Numerous case studies, applied examples and simulations across a wide spectrum of engineering projects highlight such diverse factors as:   ·         project safety ·         environmental impacts ·         societal reactions ·         time and cost overruns ·         project quality ·         legal issues ·         economic and financial considerations ·         political risk   The text is written in a down-to-earth style that demystifies the concepts, thereby enabling the reader to grasp the fundamentals of managing risk.   The author, a consulting engineer with over 30 years of experience in diverse international projects, has written over 20 books on engineering practice and brings a wealth of practical knowledge to the reader.   This text will be indispensible for undergraduates and graduates looking for practical, grassroots-level information on how to deal with uncertainties and manage risk, and for professionals active in engineering project management.